SAT0244 Association Between Spondyloarthritis and Takayasu Arteritis: a Study of 14 Cases. (9th June 2015) - Rivière, E.; Arnaud, L.; Ebbo, M.; Allanore, Y.; Claudepierre, P.; Dernis, E.; Ziza, J.M.; Philippe, P.; Richez, C.; Soubrier, M.; Miceli-Richard, C.; Mariette, X.; et al.
Abstract : Background: Spondyloarthritis (SpA) and Takayasu arteritis (TA) are two chronic inflammatory diseases; their association is rare but has already been described in the literature. Objectives: The aim of this study was to describe the clinical features of patients suffering from SpA associated with TA and to identify some characteristics of SpA patients that could be suggestive of TA. Finally, we analyzed treatments that were generally used in this clinical context and their efficacy in TA. Methods: This retrospective study collected patients' cases from 10 medical centers in France. Data collection relied on a call for observations on behalf of the Club Rhumatismes et Inflammation. A standardized questionnaire was established and validated by the investigators. Results: We included 14 patients, 10 of them were women. The median age at SpA diagnosis was 43.5 years (ranging from 19 to 63). Subtypes of SpA were: ankylosing spondylitis (n=11), psoriatic arthritis (n=2) and SAPHO syndrome (n=1). HLA-B27 was positive in 3 cases, negative in 9 cases and unknown in 2 cases. SpA was diagnosed before TA in 13 cases (median time of 4.5 years). During SpA patients' follow-up, TA revealing symptoms were: clinical detection of a pulse diminution/abolition (3/14), superior limb claudication (2/14), and vascular sound (2/14). Other TA diagnoses were made by the exploration of inflammatory cervical pain (1/14), or the radiological detection of radial artery thrombosis (1/14). TA was confirmed by CT (11/14) and/or PET (6/14) or anatomopathology (1/14). Laboratory tests shown increased acute phase reactants in all cases, C-reactive protein being ≥25mg/L in 71% of the cases; systemic inflammation was the revealing factor for TA in 6 cases. Seven patients were treated with anti-TNF: 2 with adalimumab, 4 with etanercept (among whom one required a switch to infliximab and another required a switch to adalimumab, and then to golimumab) and 1 with infliximab. Anti-TNF treatment was introduced in 5/7 cases after TA diagnosis. Vascular surgery was necessary for 4 patients. Conclusions: Association of SpA and TA is probably not coincidental. The recent findings of double negative T cells expressing IL-23 receptor in the aorta of mice presenting with a model of SpA supports this association [1] . The careful peripheral pulse palpation and vessels auscultation should be systematic and stay the first alert to TA diagnosis in SpA patients. Moreover, increased acute phase reactants during SpA follow-up, without alternative explanation, should alert physicians and lead to screen patients for TA, as well as for an inflammatory bowel disease. Finally, the identification of this association has therapeutic implications since anti-TNF alpha have already demonstrated their efficacy in both diseases as observed in our study. References: Sherlock et al., IL-23 induces spondyloarthropathy by acting on ROR-γt+ CD3+CD4−CD8− entheseal resident T cells. Acknowledgements: Club Rhumatisme et Inflammation Disclosure of Interest: None declared